A patient with an ectopic sphenoid bone TSH secretory adenoma: Case report and review of the literature - Kumar, Shejil; Phang, Cun An; Ni, Huajing; Diamond, Terrence (Frontiers in Endocrinology, 2022)
Ectopic thyroid-stimulating hormone (TSH)oma located outside the sella turcica is exceedingly rare and can be associated with significant diagnostic delay. The clinical presentation depends on the anatomical location and size of the ectopic tumor and the degree of thyrotoxicosis. A 71-year-old woman presented with goiter and thyrotoxicosis. Initial investigations revealed elevated free thyroxine (fT4) and tri-iodothyronine (fT3) with inappropriately high-normal TSH. Assay interference was unlikely, pituitary magnetic resonance imaging (MRI) scan was reported as “normal,” and germline sequencing was negative for thyroid hormone receptor ß pathogenic variants. One year later, total thyroidectomy for enlarging symptomatic goiter and suspicious nodule revealed multifocal microscopic papillary thyroid carcinoma. Six years later, she presented to an ear, nose, and throat surgeon with nasal congestion, and a sphenoid bone mass was discovered on nasoendoscopy and imaging. Ectopic TSHoma was confirmed on surgical resection, and a review of the initial pituitary MRI scan revealed the mass which had initially been missed. This is the first reported case of an ectopic TSHoma located in the sphenoid bone. Ectopic TSHoma should be considered in patients with inappropriate TSH secretion when more common differentials are excluded including thyroid hormone resistance or pituitary TSHoma.